2007
DOI: 10.1021/la701848c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Surface Properties of Amino-Acid-Modified Carbonate-Containing Hydroxyapatite Particles

Abstract: The surface properties (nature, strength, and stability of interaction of functional groups) and bulk morphologies of a series of amino-acid-functionalized carbonate-containing hydroxyapatite (CHA) particles were investigated. It was found that the amino acids were both occluded in and presented on the surface of the CHA particles. Furthermore, their presence enhanced particle colloidal stability by retardation of Ostwald ripening and in some cases increasing the magnitude of the zeta-potential. Measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 57 publications
7
76
1
Order By: Relevance
“…As is evident from table 2, almost all AAs are able to inhibit both HA particle growth and crystal growth, irrespective of their electrical charges. However, charged AAs, such as Glu, Asp, arginine (Arg) and lysine (Lys), show a significantly stronger effect than non-charged ones [6,7,23]. This is related to the presence of stronger interactions between charged AAs and Ca 2þ and PO 4 32 ions, as well as with the surface of HA particles already formed in solution.…”
Section: Amino Acids Dissolved In Solutionmentioning
confidence: 99%
See 3 more Smart Citations
“…As is evident from table 2, almost all AAs are able to inhibit both HA particle growth and crystal growth, irrespective of their electrical charges. However, charged AAs, such as Glu, Asp, arginine (Arg) and lysine (Lys), show a significantly stronger effect than non-charged ones [6,7,23]. This is related to the presence of stronger interactions between charged AAs and Ca 2þ and PO 4 32 ions, as well as with the surface of HA particles already formed in solution.…”
Section: Amino Acids Dissolved In Solutionmentioning
confidence: 99%
“…They showed that a negatively charged AA, Asp, has the highest affinity for HA (table 3). However, Jack et al measured a stronger affinity to HA for a positively charged AA, Lys, and attributed this to the decrease in repulsion between the net negative charges of HA surface and any negatively charged segments on the AA side chains [6]. Despite their differences, both these sets of results imply a stronger effect of charged ( positive or negative) AAs, such as Arg and Asp on inhibiting HA precipitation.…”
Section: (Fix)mentioning
confidence: 99%
See 2 more Smart Citations
“…values obtained from electrophoretic mobility measurements versus tangential/transversal streaming potential/current measurements). [30][31][32][33][34] In spite of the large variability, it has been gaining consensus that synthetic HA has an isoelectric point (IEP) between pH 5-7. 30,35 The sign of the zeta potential obtained in the present work is negative at pH 6 which is consistent with the IEP.…”
Section: Zeta Potential Of Hydroxyapatite Substrates With Different Pmentioning
confidence: 99%